2002
DOI: 10.1016/s0014-5793(02)02608-x
|View full text |Cite
|
Sign up to set email alerts
|

A metacaspase of Trypanosoma brucei causes loss of respiration competence and clonal death in the yeast Saccharomyces cerevisiae

Abstract: Metacaspases constitute a new group of cysteine proteases homologous to caspases. Heterologous expression of Trypanosoma brucei metacaspase TbMCA4 in the budding yeast Saccharomyces cerevisiae resulted in growth inhibition, mitochondrial dysfunction and clonal death. The metacaspase orthologue of yeast, ScMCA1 (YOR197w), exhibited genetic interaction with WWM1 (YFL010c), which encodes a small WW domain protein. WWM1 overexpression resulted in growth arrest and clonal death, which was suppressed by concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
0
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 43 publications
0
104
0
7
Order By: Relevance
“…Recently it has been suggested that the actD gene, MXAN3216, is a cysteine protease homolog that belongs to clan CD, which includes family C14 of caspase-like enzymes EC 3.4.22.36 and which is directed toward particular proteins (1,4,63,65). Members of this family have a His/Cys catalytic dyad around which sequence is conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been suggested that the actD gene, MXAN3216, is a cysteine protease homolog that belongs to clan CD, which includes family C14 of caspase-like enzymes EC 3.4.22.36 and which is directed toward particular proteins (1,4,63,65). Members of this family have a His/Cys catalytic dyad around which sequence is conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling of the threedimensional protein structure of para-and metacaspases indicates significant tertiary structure homology to animal caspases (the so-called caspasehemoglobinase fold). Mutational studies in Trypanosoma brucei first suggested that metacaspases function as Cys proteinases (Scallies et al, 2002). It was recently shown that the only metacaspase present in Brewer's yeast (Saccharomyces cerevisiae) displays caspase-like proteolytic activity that is activated when yeast is stimulated by H 2 O 2 to undergo apoptosis (Madeo et al, 2002).…”
Section: Caspase Tertiary Structurementioning
confidence: 99%
“…Presumably, early ancestors of plants and animals had minimal apoptotic machinery, with the more complex PCD systems emerging with the evolution of metazoans. Whereas most metacaspase genes have only been characterized in silico, their genetic signatures have been directly linked to caspase activity and the mediation of PCD in yeast (20) and trypanosomes (21). Metacaspases are also essential for PCD execution in plants despite possessing an altered substrate specificity compared with canonical caspases (22,23).…”
mentioning
confidence: 99%